Specific physical training in elite male team handball - Wagner, H.; Gierlinger, M.; Adzamija, N.; Ajayi, S.; Bacharach, D. W.; von Duvillard, S. P. (The Journal of Strength and Conditioning Research, 2017)
Specific physical training in elite team handball is essential for optimal player's performance; however, scientific knowledge is generally based on temporary training studies with subelite athletes. Therefore, the aim of the study was to analyze the effects of specific physical training in an elite male handball team over the entire season. Twelve players of a male handball team from the First Austrian Handball League conducted a 1-year specific physical training program in addition to their normal (team handball techniques and tactics) weekly training. Performance was measured with 5 general and 4 specific tests as well as game statistics during competition. Repeated measures analysis of variances and paired sample t-test were used to analyze differences in performance during training. We found a significant increase in oxygen uptake, offense time, defense time, fast break time, and jump height in the specific tests. Game performance statistics revealed a lower throwing percentage in the hosting team (59%) compared with the rival teams (63%). Our results indicated that specific endurance and agility are an acceptable modality in elite male team handball. However, performance in competition is strongly influenced by specific techniques and tactics. We recommend to strength and conditioning professionals that they tailor strength and power training, coordination and endurance as specific as possible, using free weights, agility exercises that include change in direction and jumps as well as short (10-15 seconds) high-intensity intervals.